2017
DOI: 10.5897/ajar2017.12138
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of Malawian orange local maize variety in nutrients, cookability and storability

Abstract: The objectives of this study were to evaluate the potential of an orange Malawian local maize variety MW5021 by comparing with a hybrid variety DKC-9089 for nutritional quality and processing properties such as proximate and mineral composition as well as pasting and thermal properties of the flour, and resistance against Prostephanus truncatus infestation during storage of the grain. Maize plants sampled for the experiments were cultivated under three different fertilizer applications, namely 0, 92 and 184 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
2
3
1
Order By: Relevance
“…Orange maize from Dedza (2.28%) displayed the highest ash content and the lowest was discovered in purple maize from Mzimba (1.10%). Tis is similar to what Murayama et al [35] reported. Diferences in ash content in PLMVs were attributed to diferences in maize varieties and genetic make up but also environmental diferences in mineral composition.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Orange maize from Dedza (2.28%) displayed the highest ash content and the lowest was discovered in purple maize from Mzimba (1.10%). Tis is similar to what Murayama et al [35] reported. Diferences in ash content in PLMVs were attributed to diferences in maize varieties and genetic make up but also environmental diferences in mineral composition.…”
Section: Resultssupporting
confidence: 91%
“…Our fndings revealed that red maize from Dedza (12.57%) had the highest protein content than what Shaista et al [2] reported (12.45%) and Mzimba (10.16%) orange maize reported the lowest. Te fndings are in line with what Murayama et al [35] reported in a study that was also done in Malawi on orange maize. Te diferences in protein content observed in this study would be a result of the interaction between environmental factors and the genetic makeup of the varieties which infuences protein metabolic processes within the plants [26].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In vulnerable regions, farmers have explored more accessible alternatives, such as the application of ground powders from repellent native plants to stored kernels (Midega et al, 2016) and the use of local varieties with some degree of natural resistance. Native maize landraces have been identified as some of the best natural sources of resistance, leading to loss reduction to less than 10% without cost increment (Daiki et al, 2017;García-Lara and Bergvinson, 2013;Mwololo et al, 2012). However, their yield is often very low.…”
Section: Strategies For Reduction Of Postharvest Food-grain Lossesmentioning
confidence: 99%
“…Thus, alternatives such as repellent ground powders (Midega et al, 2016) and local varieties and native landraces with natural pest resistance (García-Lara and Bergvinson, 2013;Gitonga et al, 2013;Mwololo et al, 2013;Mlambo et al, 2017) have been considered. As landraces often have comparatively low yields (Daiki et al, 2017), breeding programmes have been introduced globally to develop insectresistant varieties with increased yields (Abebe et al, 2009;Tefera et al, 2011Tefera et al, , 2016. For this purpose, the traits and their mechanisms of action associated with postharvest pest resistance need to be identified described.…”
Section: Introductionmentioning
confidence: 99%